Implementasi Media Poster Mini sebagai Sarana Edukasi Pencegahan Pelecehan Seksual pada Anak di SDN 243 Palembang - Rina Oktaviana; Patri Afrianti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
The rapid development of information and communication technology has expanded access to information but has also increased the risk of sexual abuse against children, both through direct interactions and digital media. The method used in this program was an educational socialization session utilizing mini posters to provide students at SD Negeri 243 Palembang with knowledge on the prevention of child sexual abuse from an early age. The results showed that the educational program conducted by the Palembang Office of Women's Empowerment and Child Protection (DP3A) successfully implemented mini posters as an effective educational medium. The posters supported the delivery of information in a simple, engaging, and age-appropriate manner, making it easier for students to understand the material. Based on observations during the activity, students demonstrated a good understanding of the importance of personal safety, were able to recognize inappropriate behaviors, and understood the appropriate actions to take if they experienced or witnessed sexual abuse.